Design of a Business Branch of Rawit Seeds Alon Farm in Surade District Sukabumi Regency - Muhammad Rif’at Reihan Aula Arifin; Endang Chumaidiyah; Maria Dellarosawati Idawicaksakti (Budapest International Research and Critics University, 2022)
This study discusses how to make a business feasibility study that must be carried out by every company that will invest or a new business. The discussion starts from the scope of the study of market aspects, technical/operational aspects and financial or financial aspects accompanied by case studies. ALON Farm is one of the authors' objects in this study, which is a cayenne pepper seed business located around the Surade area. Starting from a company that was overwhelmed in providing cayenne pepper seeds, ALON Farm emerged because by promising to fulfill the needs and demands of local farmers. The purpose of this research is to propose and plan the opening of a branch of the cayenne pepper seed business that is deemed necessary in connection with the need for the supply of chili seeds in the Surade area and its surroundings. With the feasibility study method through market aspect analysis from the company's past data for the past 3 years, then the data is processed by using the Linear Trend forecasting method in order to get the estimated total sales for the next 3 years. The company targets production to exceed the estimated sales value with an allowance of 0.1% from the estimated sales. For the technical and financial aspects, secondary data obtained from various sources is used. The results of the feasibility calculation show the NPV value for the calculation period in this study, which is 1-36 months, is Rp103.294.565, the IRR value is 24,42% and the PP is 2,569 years. Because the value of NPV > 0 and IRR > MARR, the opening of the ALON Farm company can be said to be feasible